Ultra-Sound Guided Fine Needle Aspiration Cytology in Diagnosis of Space Occupying Lesions of Liver with Special Emphasis on Hepato-Cellular Carcinoma - 2 Senior Prof.D, Dr. Mangilal Choudhary , (International Journal of Scientific Research and Management (IJSRM), 2017)
BackgroundThe evaluation and management of various hepatic lesions is a common clinical problem and theirappropriate clinical management depends on accurate diagnoses.Aims:To study the cytomorphological features of distinctive non-neoplastic and neoplastic lesions of the liverand to evaluate the sensitivity, specificity and diagnostic accuracy of ultrasonography (USG)-guided fineneedle aspiration cytology (FNAC) in the diagnosis of liver diseases.Materials and Methods:The study was performed on patients who came with SOL in liver on ultrasonography, with normalrange of prothrombin time index in SMS hospital, Jaipur. Procedure was performed on 172 patientsfrom 2 January 2016 to 16 sepetember 2016. USG Guided FNAC performed after getting an informedconsent & with the help of a radiologist. Relevant clinical and serological details were obtained fromevery patient .Results:The mean age at presentation 56.47 years (25-95 years), ratio was almost equal male to female , malepatient were 91(52.9%) and female were 81(47.09%) out of 172. Adequate sample were 148(86.04) andinadequate sample were 24 out of 172 patients. The cytological diagnosis of non neoplastic lesion weretotal 10 in which granuloma 01(10%),liver abscess 4(40%),regenerating nodule 1(10%) , fatty liver2(20%), cystic lesion 1(10%) and inflammatory lesions 1(10%). Neoplastic lesion were(135) morecommon than non neoplastic lesions . The majority of neoplastic lesion were metastatic tumor104(77.03%), followed by primary HCC23 (17.3%), unclassified malignancies 4(2.96%),cholangiocarcinoma 4 (2.96%) out of total 135 cases. The overall diagnostic accuracy of FNAC was97.82% with a sensitivity and specificity of 96.87 and 100% respectively.Conclusion - USG-guided FNAC of the liver is a safe, simple, cost-effective and accurate method forcytological diagnosis of hepatic diffuse, focal/nodular and cystic lesions with good sensitivity andspecificity